2018
DOI: 10.1136/bcr-2018-224611
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced autoimmune hepatitis associated with turmeric dietary supplement use

Abstract: Turmeric dietary supplement sales, which accounted for US$69 million in spending in 2016, have been increasing exponentially in the USA, making this one of the most popular botanical supplements sold in the USA. Herbal supplement use, which is generally regarded as safe by consumers, is not usually reported to healthcare providers. We reported here on a case of autoimmune hepatitis, occurring in a 71-year-old woman taking turmeric dietary supplements for the maintenance of cardiovascular health, which resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 62 publications
(24 reference statements)
1
27
0
Order By: Relevance
“…While touted for its many benefits, including paradoxically, anti‐inflammatory effect in non‐alcoholic steatohepatitis, this case illustrates the significant risk of hepatotoxicity associated with turmeric. To date, there has been only one other case reported in current literature to support this finding . Our case highlights the importance of clinicians and consumers to remain diligent of adverse effects when utilising natural or alternative medicines.…”
supporting
confidence: 65%
“…While touted for its many benefits, including paradoxically, anti‐inflammatory effect in non‐alcoholic steatohepatitis, this case illustrates the significant risk of hepatotoxicity associated with turmeric. To date, there has been only one other case reported in current literature to support this finding . Our case highlights the importance of clinicians and consumers to remain diligent of adverse effects when utilising natural or alternative medicines.…”
supporting
confidence: 65%
“…Regarding adverse effects, a number of severe adverse effects have been reported when given orally [1618], topically [19], vaginally [20], and intravenously [21]. Mild liver function test derangement has been reported in approximately 5% of cases in randomized controlled trials [22], with one report of drug induced autoimmune hepatitis reported recently [22]. The potential for drug interactions has been recognized, with dose-dependent inhibition of cytochrome p450 subtypes CYP3A4 and CYP1A2 in the liver [23] and intestines [24] identified.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent reports of liver diseases related to curcumin attracted the medical community's attention to its possible hepatotoxicity [203]. Whether this effect belongs to curcumin molecule or other possible contamination has to be elucidated.…”
Section: Curcumin Toxicitymentioning
confidence: 99%